P038 Comparing the Efficacy and Safety of Subcutaneous Vedolizumab Versus Adalimumab for the Treatment of Ulcerative Colitis: A Network Meta-Analysis. (December 2019) - Jairath, Vipul; Chan, Keith; Lasch, Karen; Keeping, Sam; Agboton, Christian; Blake, Aimee; Jansen, Jeroen; Patel, Haridarshan
Abstract : BACKGROUND: Vedolizumab (VDZ), a gut-selective monoclonal α4β7 integrin antibody, is approved for the treatment of moderately to severely active ulcerative colitis (UC) and Crohn's disease. Intravenous (IV) VDZ was recently shown to be superior to subcutaneous (SC) adalimumab (ADA) in VARSITY (1 ), the first head-to-head randomized controlled trial (RCT) of biological therapies in UC. No comparative efficacy or safety data versus ADA exist for VDZ SC, a new formulation in development (2 ). To generate estimates of the comparative efficacy and safety of VDZ SC versus ADA, we conducted a network meta-analysis (NMA) of RCTs. METHODS: The NMA was conducted using results from a targeted literature review that identified RCTs of both VDZ and ADA: GEMINI 1, VISIBLE 1, ULTRA-2, and VARSITY. In the former two trials, responders were rerandomized at the end of induction, whilst the latter two trials were treat-through designs. To adequately analyze these trials in one network of evidence, efficacy outcomes were assessed conditionally upon response at start of maintenance. For treat-through studies, this was response at 6/8 weeks. Efficacy outcomes in the maintenance period were response and remission at 52/54 weeks. Safety outcomes were overall adverse events (AEs), serious AEs (SAEs), overall infections, serious infections, and AEs leading to discontinuation as reported at 52 weeks. Odds ratios (OR) with 95% credible intervals (CrI) were estimated using probit and binomial NMA models. ADA SC 40 mg Q2W, VDZ IV 300 mg Q4W, and VDZ IV 300 mg Q8W were all compared against VDZ SC 108 mg Q2W (reference group). RESULTS: ADA had lower rates for maintenance of response and remission relative to VDZ SC, but this was not statistically significant (ORs with 95% Crl: 0.60 [0.33, 1.08] and 0.59 [0.33, 1.09], respectively). Although overall AEs were significantly higher with ADA compared with VDZ SC (OR 2.02 [1.04, 3.89]), other safety outcomes were similar: overall infections, OR 1.86 (0.94, 3.77); serious AEs, OR 1.41 (0.54, 3.75); serious infections, OR 0.39 (0.05, 2.73); AEs leading to discontinuation, OR 2.58 (0.80, 9.44). As expected, VDZ IV had similar maintenance efficacy and safety outcomes relative to VDZ SC. CONCLUSION(S): Results from this indirect treatment comparison suggest that VDZ SC may achieve higher rates of maintenance response and remission among responders at start of maintenance than ADA and is associated with a lower risk of overall AEs. In the absence of a head-to-head trial between VDZ SC and ADA SC, these findings support a favorable benefit-risk profile of VDZ SC in UC.